The Nevanlinna-type formula for the matrix Hamburger moment problem - Zagorodnyuk, S. M. (Methods of Functional Analysis and Topology, 2012)
In this paper we obtain a Nevanlinna-type formula for the matrix Hamburger moment problem. We only assume that the problem is solvable and has more than one solution. We express the matrix coefficients of the corresponding linear fractional transformation in terms of the prescribed moments. Necessary and sufficient conditions for the determinacy of the moment problem in terms of the given moments are obtained.